Topical application of double-stranded RNA molecules containing sequences of Tomato leaf curl virus and Cucumber mosaic virus confers protection against the cognate viruses. (December 2019) - Namgial, Tsewang; Kaldis, Athanasios; Chakraborty, Supriya; Voloudakis, Andreas
Abstract: The Tomato leaf curl virus (ToLCV) is a bipartite (DNA) geminivirus whereas Cucumber mosaic virus (CMV) is a tripartite RNA virus, both infecting a wide range of host plants. RNAi that is triggered by double-stranded RNA (dsRNA) molecules, is a powerful means to control plant viruses in transgenic plants, as well as in a non-transgenic manner in a process designated as 'RNA-based vaccination'. DsRNA molecules were made for AC1/AC4, AV1/AV2 (overlapping regions of ToLCV), AC1/AC4_AV1/AV2 (designated as fusion construct), CMV-2b and CMV-2b_ToLCV-AV1/AV2 (designated as hybrid construct, containing regions from two different viruses). In tomato ( Solanum lycopersicum ), dsRNAs for AC1/AC4, AV1/AV2, AC1/AC4_AV1/AV2 and CMV-2b_ToLCV-AV1/AV2 conferred 45%, 60%, 50% and 55% protection against ToLCV, respectively. Experiments with tobacco ( Nicotiana tabacum ) showed that the dsRNA construct CMV-2b_ToLCV-AV1/AV2 conferred 33.3% protection against CMV, while CMV-2b provided 40% protection. The present study reported that the dsRNA exhibits systemic transport in tomato. This is the first case where RNA-based vaccination is functional for a bipartite geminivirus and where a single dsRNA molecule could protect against two tomato-infecting viruses, namely a DNA (ToLCV) and an RNA (CMV) plant virus. Highlights: Exogenous application of double stranded RNA provided protection against ToLCV and CMV. A hybrid dsRNA molecule, containing the desired targets from two viruses, provided control against the respective viruses. DsRNA exhibits systemic transport in tomato.